Cellular Senescence in Diabetes Mellitus: Distinct Senotherapeutic Strategies for Adipose Tissue and Pancreatic β Cells - Murakami, Takaaki; Inagaki, Nobuya; Kondoh, Hiroshi (Frontiers in Endocrinology, 2022)
Increased insulin resistance and impaired insulin secretion are significant characteristics manifested by patients with type 2 diabetes mellitus (T2DM). Insulin resistance is accompanied by accumulation of dysfunctional adipose tissues. In addition, dysfunction of pancreatic β-cells impairs insulin secretion and β-cell mass diminishes with age. Moreover, both obesity and hyperglycemia-related metabolic changes in developing diabetes are associated with accumulation of senescent cells in multiple organs. Senolysis, the removal of senescent cells, can be a promising therapeutic approach to prevent or improve aging-related diseases, including diabetes, although the pathophysiological involvement of cellular senescence in diabetes is not fully understood. In the clinical application of senotherapy, tissue-dependent senescent cells are increasingly being recognized as an issue to be solved. Recent studies have observed highly heterogenic and complex senescent cell populations that serve distinct roles among tissues, various stages of disease, and different ages. In high-fat-diet induced diabetes with obesity, mouse adipose tissues display accumulation of p21Cip1-highly-expressing (p21high) cells in the early stage, followed by increases in both p21high and p16INK4a-highly-expressing (p16high) cells in the late stage. Interestingly, elimination of p21high cells in visceral adipose tissue can prevent or improve insulin resistance in mice with obesity, while p16high cell clearance is less effective in alleviating insulin resistance. Importantly, in immune-deficient mice transplanted with fat from obese patients, dasatinib plus quercetin, a senolytic cocktail that reduces the number of both p21high and p16high cells, improves both glucose tolerance and insulin resistance. On the other hand, in pancreatic β cells, p16high cells become increasingly predominant with age and development of diabetes. Consistently, elimination of p16high cells in mice improves both glucose tolerance and glucose-induced insulin secretion. These findings clearly indicate that features of diabetes are partly determined by which or where senescent cells reside in vivo, as adipose tissues and pancreatic β cells are responsible for insulin resistance and insulin secretion, respectively. In this review, we summarize recent advances in understanding cellular senescence in adipose tissues and pancreatic β cells in diabetes. We review the different potential molecular targets in adipose tissues and pancreatic β cells, and propose a dual-target tailored approach in senotherapy against diabetes.